Taman Ujung Soekasada: Analysis of Physical Attributes and Urban Heritage Management - I Gede Wyana Lokantara; Dessy Mayasarib; Farisa Maulinam Amo (International Journal of Applied Sciences in Tourism and Events, 2021)
The revitalization and preservation of Taman Ujung Soekasada cultural heritage area make this building used as a heritage tourism destination in Karangasem. The purpose of this research is to analyze the uniqueness of Taman Ujung Soekasada cultural heritage as heritage tourism and to find out people's perceptions about the development of the area into a tourist destination in Amlapura City. This study uses a mixed-method that combines two analyzes, namely quantitative and qualitative. Quantitative analysis was obtained through a perceptual survey of one hundred respondents to find out their opinion on the management of Ujung Soekasada Park as a heritage tourism area. Qualitative analysis was carried out by identifying spatial conditions, spatial planning, and building patterns in Ujung Soekasada Park, Amlapura. The physical elements contained in the traditional architecture of Taman Ujung Soekasada have a high value if it can be managed properly to become a tourist destination, especially to provide added value to community economic activities such as increasing micro-businesses, selling local community handicrafts, staging cultural arts and activities. other. Based on the results of the analysis, it is obtained the identification of the perceptions of the visitor community and tourism actors that they strongly agree to use Ujung Soekasada Park as a cultural tourism area by displaying the potential of traditional works of buildings, with a percentage of 86.57% hope that it can encourage tourists to come to Amlapura City, so that it can encourage progress of community economic activities around the tourist center.